The Effect of Administration of Sapodilla Leaf Extract Cream (Manilkara Zapota (L.) P. Royen) On the Expression of PDGF And Il-10 - Maharani, Sahara; Sumarawati, Titiek; Hermansyah, Dedi (Journal of Biomedicine and Translational Research, 2024)
Background: Sunburn is an acute inflammatory skin condition caused by exposure to UV rays. Excessive exposure increases the production of  ROS which, if accumulated, can lyse growth factors, one of which is PDGF and also form IL-10 immune suppression. This condition can be influenced by providing antioxidants and anti-inflammatories such as those contained in sapodilla leaf extract (Manilkara zapota (L.) P. Royen) which has many benefits such as anti-inflammatory, anti-pyretic, anti-tumor, antioxidant, anti-microbial, anti- diabetic, anti-lipid and anti-aging. In previous research, the polyphenol content in Sapodilla leaves was a potential source of inhibiting ROS. However, until now the role of Sapodilla leaf extract on UVB burns has not been studied.Objective: The aim of this research is to determine the effect of administering Sapodilla leaf extract cream on PDFG and IL-10 in Wistar rats that experienced burns due to exposure to UVB.Method: Experimental research with a post test only control group design approach. This research used 24 Wistar rats exposed to UVB rays which were divided into 4 groups (normal control, control with cream, 25% Sapodilla leaf extract cream, and 50% Sapodilla leaf extract cream). The ELISA (Enzyme-Linked Immunosorbent Assay) method was used to analyze PDGF and IL-10 levels in skin tissue.Results: The highest ratio of PDGF levels was found in (K3) 2.915 ± 0.368. The results of the one way Anova analysis had a p value of 0.024 (p<0.05) which stated that there were significant differences between treatment groups. In IL-10 levels there was an increase in K3 255.9 ± 35,563. In IL-10, the results of one way Anova analysis had a p value of 0.240 (p>0.05), which stated that there were no significant differences between treatment groups.Conclusion: Administration of sapodilla leaf extract cream at a dose of 25% had a significant effect on increasing PDGF levels and a slight increase in IL-10 in mice that experienced burns due to exposure to UVB.